Gastric Small-Cell Carcinoma Found on Esophagogastroduodenoscopy: A Case Report and Literature Review - Natassja Frances; Simon B. Zeichner; Michael Francavilla; Mike Cusnir (Case Reports in Oncological Medicine)
Introduction. Characterized as an undifferentiated, neuroendocrine tumor arising from totipotent stem cells, small-cell carcinoma (SCC) most commonly arises from the lung. Extrapulmonary small-cell carcinomas (ESCC) are rare and account for only four percent of SCC. Gastric ESCC, more commonly seen in Japanese male patients in their seventh decade of life, accounts for approximately 0.1 percent of ESCC. Case Presentation. A 75-year-old Hispanic male presented with a several week history of worsening epigastric pain with nausea and vomiting. Computer tomography (CT) of the abdomen and pelvis showed a large heterogeneous mass involving the posterior gastric wall with diffuse extension into the gastric cardia. Esophagogastroduodenoscopy (EGD) revealed a large fungating mass in the lesser curvature of the stomach. Biopsy of the mass revealed small-cell carcinoma of the stomach. The patient was diagnosed with extensive/stage 4 disease and started on chemoradiation. Discussion. Our case, of a very rare condition highlights, the importance of recognizing atypical pathologic diagnoses. More research will need to be conducted with GSCC patients in order to better characterize disease pathogenesis, genetic mutations, and optimal disease management. The hope is to identify biomarkers that will identify patients earlier in their disease course when cure is possible.